DUKUNGAN SOSIAL ORANG TUA SEBAGAI FAKTOR PELINDUNG DALAM MENGHADAPI TANTANGAN PISIKOLOGIS ANAK - Taka Abdan Syakura; Meyco Putra Herwanto; Anthera Aga Purnashakti; Alvin Maretias Pradiptya; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
Social support from parents can be an important protective factor in dealing with children's psychological challenges. The purpose of this article is to examine the role of parental social support in helping children overcome the mental health challenges they face. Qualitative and quantitative approaches were used in collecting and analyzing information from various literatures and journals on the subject. The findings in this journal suggest that parental social support, whether emotional, instrumental or informational, can play an important role in helping children overcome psychological challenges such as stress, anxiety, depression and behavioral problems. Good parental social support can provide protection and reduce the negative impact of mental health challenges on children. It can also increase children's resilience in the face of mental health challenges, help them develop social skills, improve adaptability, and improve the quality of the parent-child relationship. However, the role of parental social support can also be influenced by contextual factors such as culture, social environment and individual factors. Therefore, it is important for parents, practitioners and policy makers to understand the importance of social support in addressing children's mental health challenges and implement appropriate strategies to improve parental social support.This journal aims to be a reference for researchers and practitioners in psychology and other related fields to understand the important role of parental social support as a protective factor in dealing with mental health challenges in children. In addition, we hope that this magazine can make a meaningful contribution to improving the quality of life of children and families. Keywords: Social support, parents, protective factors, psychological challenges, children.